2021
DOI: 10.1093/eurheartj/ehab724.3303
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong dietary omega-3 fatty acid reverses cardiac and vascular dysfunction via MMP-2 modulation in aged mice

Abstract: Background Aging has a remarkable effect on the cardiovascular system, and negatively causes structural and functional changes in the heart including diastolic/systolic dysfunction and left ventricular (LV) dyssynchrony, as well as, arterial stiffness which may develop to heart failure with preserved ejection fraction (HFpEF) in aged adults. We recently showed that the plant-derived omega-3-fatty-acid α-linolenic-acid (ALA) has emerged to confer potential protective effects against cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Acetate could also regulate epigenetic-SASP interplay in PAA-treated ECs, where it downregulates VCAM1 and alleviates endothelial dysfunction. As we and others exhibited, IL6 underlies vascular premature aging and atherosclerotic CVD 24 , whereas acetate at least in HUVEC can inhibit the production of IL-6 and IL-8 and subsequently reduce VCAM1mediated cell adhesion 51 . In line with this, our findings revealed that acetate, by downregulating IL6-CaMKII, reduces HDAC4 S632 phosphorylation and stabilizes its nuclear localization, which thereby decreases VCAM1 expression.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Acetate could also regulate epigenetic-SASP interplay in PAA-treated ECs, where it downregulates VCAM1 and alleviates endothelial dysfunction. As we and others exhibited, IL6 underlies vascular premature aging and atherosclerotic CVD 24 , whereas acetate at least in HUVEC can inhibit the production of IL-6 and IL-8 and subsequently reduce VCAM1mediated cell adhesion 51 . In line with this, our findings revealed that acetate, by downregulating IL6-CaMKII, reduces HDAC4 S632 phosphorylation and stabilizes its nuclear localization, which thereby decreases VCAM1 expression.…”
Section: Discussionmentioning
confidence: 59%
“…3e). Since glutathione peroxidase converts oxidized glutathione (GSSG) to its reduced form (GSH), a key cellular ROS-scavenger 24 , we measured GPx1 transcriptional levels in baseline conditions and upon exposure to exogenous PAA (as "stress condition"). Levels of Gpx1 transcripts showed a significant reduction in PECs in stress condition induced by PAA, supporting a role of PAA in counteracting simultaneous antioxidant defense and inducing oxidative stress (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, diabetic cardiomyopathy has been considered as a cardiac disease of aging, and its development and progression has been strongly associated with accelerated ROS‐induced oxidative stress and mitochondrial dysfunction in cardiac cells (Kayama et al., 2015). Combined relatively low endogenous antioxidant capacity and increased ROS levels in the heart has been also observed in heart failure with preserved ejection fraction (HFpEF), which comprises >50% of all HF cases worldwide (Jasinska‐Piadlo & Campbell, 2023; Saeedi Saravi et al., 2023). In diabetic patients, circulating high glucose and altered insulin signaling are associated with increased ROS generation and susceptibility to oxidative responses in the heart, leading to tissue remodeling, ventricular hypertrophy, and impaired systolic and diastolic function (Huo et al., 2023; Nishio et al., 2004).…”
Section: H2o2 and Other Rosmentioning
confidence: 99%